Self-Supervised Learning for Visual Obstacle Avoidance Technical report - van Dijk, Tom (TU Delft Open, 2022)
With a growing number of drones, the risk of collision with other air traffic or fixed obstacles increases. New safety measures are required to keep the operation of Unmanned Aerial Vehicles (UAVs) safe. One of these measures is the use of a Collision Avoidance System (CAS), a system that helps the drone autonomously detect and avoid obstacles.